Gene fusion characterisation of rare aggressive prostate cancer variants-adenosquamous carcinoma, pleomorphic giant-cell carcinoma, and sarcomatoid carcinoma: an analysis of 19 cases - Alhamar, Mohamed; Tudor Vladislav, I; Smith, Steven C; Gao, Yuan; Cheng, Liang; Favazza, Laura A; Alani, Ali M; Ittmann, Michael M; Riddle, Nicole D; Whiteley, Lisa J; Gupta, Nilesh S; Carskadon, Shannon; et al. (Histopathology, 2020)
AIMS: To evaluate the molecular underpinnings of the rare aggressive prostate cancer variants adenosquamous carcinoma, pleomorphic giant-cell carcinoma, and sarcomatoid carcinoma. METHODS AND RESULTS: We retrieved 19 tumours with one or more variant(s), and performed ERG immunohistochemistry, a next-generation sequencing assay targeting recurrent gene fusions, and fluorescence in-situ hybridisation (FISH) for ERG and BRAF. Divergent differentiation included: sarcomatoid carcinoma (n = 10), adenosquamous carcinoma (n = 7), and pleomorphic giant-cell carcinoma (n = 7). Five patients had more than one variant. Four had variants only in metastases. ERG rearrangement was detected in nine (47%, seven via sequencing, showing TMPRSS2-ERG fusions and one GRHL2-ERG fusion, and two via FISH, showing rearrangement via deletion). ERG was immunohistochemically positive in the adenocarcinoma in eight of nine (89%) patients, but was immunohistochemically positive in the variant in only five of nine patients (56%, typically decreased). One patient had a false-positive ERG immunohistochemical result in the sarcomatoid component despite a negative FISH result. Two (11%) harboured BRAF fusions (FAM131A-BRAF and SND1-BRAF). CONCLUSIONS: ERG fusions are present in these rare prostate cancer variants with a frequency close to that in conventional prostate cancer (9/19, 47%). ERG immunohistochemistry usually detects rearrangement in the adenocarcinoma, but is less sensitive for the variant histology, with weak to negative staining. Adenosquamous and sarcomatoid variants can, particularly, occur together. Molecular assessment may be an additional tool in selected cases to confirm the prostatic origin of unusual tumours. The presence of two BRAF rearrangements suggests that this gene fusion may be enriched in this setting, as RAF kinase fusions have been previously reported in 1-2% of prostate cancers.
Keywords: senioři; metastázy nádorů; DNA-Binding Proteins; Carcinoma, Renal Cell; BRAF; fúzní onkogenní proteiny; Carcinoma, Giant Cell; senioři nad 80 let; genová přestavba; hybridizace in situ fluorescenční; adenoskvamózní karcinom; Carcinoma, Adenosquamous; Oncogene Proteins, Fusion; imunohistochemie; serinové endopeptidasy; prostate cancer; Middle Aged; mužské pohlaví; nádory prostaty; pleomorphic giant-cell carcinoma; karcinom z renálních buněk; SND1; Transcription Factors; Transcriptional Regulator ERG; adenosquamous carcinoma; obrovskobuněčný karcinom; Gene Rearrangement; Gene Fusion; In Situ Hybridization, Fluorescence; sarcomatoid carcinoma; transkripční faktory; Aged, 80 and over; Immunohistochemistry; Neoplasm Metastasis; Prostatic Neoplasms; Humans; High-Throughput Nucleotide Sequencing; Proto-Oncogene Proteins B-raf; lidé středního věku; ERG; vysoce účinné nukleotidové sekvenování; Serine Endopeptidases; fúze genů; protoonkogenní proteiny B-Raf; DNA vazebné proteiny; transkripční regulátor ERG; Aged; FAM131A; GRHL2; lidé; Male